Nasalance in adolescents with autism spectrum disorders. (2nd September 2020) - Kasthurirathne, Rachel; Forrest, Karen; Ross, Jared; Patel, Rita
Abstract: Purpose: Listener judgments indicate atypical nasal resonance in individuals with Autism Spectrum Disorders (ASD); however, listener perceptions are susceptible to bias and may give unreliable information about a speaker's production of nasal resonance. The current study used Nasometry to obtain an objective estimation of nasal resonance among adolescents with ASD and neurotypical controls. Method: The Nasometer II 6450 (PENTAX Medical, Lincoln Park, New Jersey) was used to collect nasalance from adolescents aged 15–17 years with ASD ( n  = 11) and matched controls ( n  = 11) across two separate speech tasks: (1) passage reading and (2) spontaneous speech. Result: Adolescents with ASD evidenced significantly higher nasalance scores compared to controls, particularly in the passage loaded with bilabial plosives and some nasals (Bobby) as well as non-nasal words extracted from spontaneous speech. In addition, adolescents with ASD had significantly higher nasalance ratios than controls. Significant group differences were driven by a subset of participants with ASD. Conclusion: Perceptual judgements of nasality noted in previous autism studies are quantified by an increase in nasal energy compared to oral energy. The current data suggest hypernasality is present in a subset of people with ASD rather than being a general feature of speech in autism.